The impact of environmental conditions on player loads during preseason training sessions in women's soccer athletes - Austin, A. B.; Collins, S. M.; Huggins, R. A.; Smith, B. A.; Bowman, T. G. (The Journal of Strength and Conditioning Research, 2021)
Our objective was to determine the impact of environmental conditions on player loads during preseason training sessions in women's soccer athletes. Eleven women's NCAA Division III soccer players (age = 20 ± 1 year, height = 167.28 ± 8.65 cm, body mass = 60.18 ± 5.42 kg, Vo2max = 43.70 ± 3.95 ml/kg/min) volunteered to wear Global Positioning System (GPS) devices (Sports Performance Tracking, Melbourne, Australia) that provided measures of training session external intensity throughout all preseason practices (n = 15). We recorded wet-bulb globe temperature (WBGT), session Rating of Perceived Exertion-Training Load (sRPE-TL), and DeltaBM during each preseason training session and set a = 0.05. The combination of WBGT, sRPE-TL, and DeltaBM explained 34% of the variance in GPS-based intensity score (proprietary measure) (F3,153 = 26.25, p < 0.001). Wet-bulb globe temperature (t156 = -2.58, p = 0.01), sRPE (t156 = 8.24, p < 0.001), and DeltaBM (t156 = 2.39, p = 0.02) were significantly associated with intensity. The DeltaBM from prepractice (60.00 ± 5.21 kg) to postpractice (59.61 ± 5.10 kg) was statistically significant (p < 0.001); however, DeltaBM from the beginning of preseason (59.87 ± 5.31 kg) to the end of preseason (59.91 ± 5.58 kg) was not significant (p = 0.89). Despite relatively low to moderate environmental conditions, increases in WBGT were associated with reductions in GPS intensity and elevated internal load via sRPE-TL. Our findings support the association between exercise intensity and WBGT, internal load, and hydration status; thus, coaches and exercise scientists should take these factors into account when monitoring or interpreting intensity metrics. Furthermore, these findings support the continued use of environmental monitoring and hydration best-practice policies to limit exercise intensity in the heat so as to mitigate excessive heat stress.